Quarrying the coasts of Crete in antiquity; some geoarchaeological considerations - Tziligkaki, Eleni (Bulletin of the Geological Society of Greece, 2018)
The paper discusses three aspects of coastal quarrying in the island of Crete, Aegean Sea, Greece; issues of chronology in regard to the Mean Sea Level in antiquity, issues of ancient technology, and issues of local marble extraction. A series of violent seismic events, the most known being the so-called Early Byzantine Tectonic Paroxysm, affected the morphology of the coastline of Crete, the coastal quarries of which are today either uplifted or sunken. Quarries of aeolianite/sandstone, limestone, marble, and beach rock are related to adjacent rock-cut fish tanks and ship sheds. Traces of the ancient exploitation such as the circular holes observed in the coastal quarries are differentiated according to their dimensions and their natural or manmade form. A preliminary report of a new site, a white marble quarry at Istron (Gulf of Merambello, eastern Crete), is added to the white marble quarries of the area and correlated with the graffiti inscribed on the islet of Prasonēsi or Vryonēsi.